Kunci Kelas Terjadwal Teknik Elektro UIN SUSKA Riau Berbasis RFID dan IoT - Maria, Putut; Akbar, Farhandhika; Ullah, Aulia; Zarory, Hilman (Jurnal Sistem Cerdas, 2023)
Currently, the Electrical Engineering classroom at Sultan Syarif Kasim Riau State Islamic University still uses conventional key. The use of conventional key in the classroom is considered impractical in it use, when there is no schedule the door is left open which causes chairs to move rooms and the use of classrooms is not according to schedule because of schedule changes occurred during the first to third week of lectures. The purpose of this research is to create a classroom security system using an automatic door lock based on the lecture schedule. The tool has two accesses by RFID tags and telegram. RFID tags can be used when the device is not connected to the internet and for emergency access. Telegram is used as a chat-based IoT device control to access the door and input the classroom schedule. The research resulted in a device for controlling classroom door locks that can only be accessed and opened according to the lecture schedule. Door access using an RFID card provides a response time in the range of 0.99 to 1.99 seconds and if using a message via telegram bot, the response time is in the range of 1.97 to 2.62 seconds.